2018
DOI: 10.1002/per.2156
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Child Personality in Effects of Psychologically Controlling Parenting: An Examination at the Level of Daily Fluctuations

Abstract: Research increasingly demonstrates the detrimental effects of psychologically controlling parenting on children's adjustment. An important and practically relevant question is whether some children are more vulnerable for the effects of psychologically controlling parenting. In the current diary study, we investigated whether daily psychologically controlling parenting relates to children's daily externalizing and internalizing problems and whether these associations depend on child personality. A total of 206… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…Consistent with this perspective, several studies have shown that personality variables could moderate relations between social factors, need satisfaction/frustration, and outcomes, although effect sizes were modest (Schüler, Wegner, & Knechtle, 2013;Mabbe, Soenenes, Vansteenkiste, & Van Leeuwen, 2016;Mabbe et al, 2018;Van Assche et al, 2018). This moderate viewpoint of universalism is consistent with the moderating effects of openness to experience on the relations between need satisfaction/frustration and well-being.…”
Section: Discussionsupporting
confidence: 62%
“…Consistent with this perspective, several studies have shown that personality variables could moderate relations between social factors, need satisfaction/frustration, and outcomes, although effect sizes were modest (Schüler, Wegner, & Knechtle, 2013;Mabbe, Soenenes, Vansteenkiste, & Van Leeuwen, 2016;Mabbe et al, 2018;Van Assche et al, 2018). This moderate viewpoint of universalism is consistent with the moderating effects of openness to experience on the relations between need satisfaction/frustration and well-being.…”
Section: Discussionsupporting
confidence: 62%
“…Consistent with this perspective, several studies have shown that personality variables could moderate relations between social factors, need satisfaction/frustration, and outcomes, although effect sizes were modest (Schüler, Wegner, & Knechtle, 2013;Mabbe, Soenenes, Vansteenkiste, & Van Leeuwen, 2016;Mabbe et al, 2018;Van Assche et al, 2018). This moderate viewpoint of universalism is consistent with the moderating effects of openness to experience on the relations between need satisfaction/frustration and well-being.…”
Section: Discussionsupporting
confidence: 58%
“…Because the number of potentially relevant personality differences is extremely large, much as the number of contextual supports and thwarts, the literature on personality by need‐relevant contextual conditions is large, and only selectively reviewed herein. Directly considering the role of Big‐Five traits, recent studies have begun addressing whether personality moderates the association between psychologically controlling parenting and outcomes, with adolescent‐perceived and parent‐reported differences in parenting being studied both at the level of individual differences (Mabbe, Soenens, Vansteenkiste, & Van Leeuwen, ) and at the level of daily, within‐person fluctuations (Mabbe, Vansteenkiste, et al, ). These studies have shown that the number of moderating effects (across different outcomes and across informants) is limited.…”
Section: Relations Between Sdt and Wttmentioning
confidence: 99%